2017
DOI: 10.7717/peerj.3298
|View full text |Cite
|
Sign up to set email alerts
|

A public dataset of running biomechanics and the effects of running speed on lower extremity kinematics and kinetics

Abstract: Background. The goals of this study were (1) to present the set of data evaluating running biomechanics (kinematics and kinetics), including data on running habits, demographics, and levels of muscle strength and flexibility made available at Figshare (DOI: 10.6084/m9.figshare.4543435); and (2) to examine the effect of running speed on selected gait-biomechanics variables related to both running injuries and running economy. Methods. The lower-extremity kinematics and kinetics data of 28 regular runners were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 31 publications
8
74
0
1
Order By: Relevance
“…It was expected that the effects of the stiff plate location on running biomechanics would depend on the running speed, due to the differences in terms of loadings and lower limb biomechanics between the slower and the faster speed. The running speed difference (slower: 3.28 ± 0.28 m/s; faster: 4.01 ± 0.27 m/s) was indeed enough to induce significant changes as previously observed (Arampatzis, Brüggemann, & Metzler, 1999;Fukuchi, Fukuchi, & Duarte, 2017), that is: the faster speed increased vertical and propulsive GRF, increased hip joint range of motion, and increased net torques and work in all lower limb joints compared to the slower speed. The lack of significant interaction effect on running biomechanics suggested that adding a stiff plate into the shoe did not require specific location among speeds performed in the present study, which mainly corresponded to speeds performed by recreational runners (Gordon et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…It was expected that the effects of the stiff plate location on running biomechanics would depend on the running speed, due to the differences in terms of loadings and lower limb biomechanics between the slower and the faster speed. The running speed difference (slower: 3.28 ± 0.28 m/s; faster: 4.01 ± 0.27 m/s) was indeed enough to induce significant changes as previously observed (Arampatzis, Brüggemann, & Metzler, 1999;Fukuchi, Fukuchi, & Duarte, 2017), that is: the faster speed increased vertical and propulsive GRF, increased hip joint range of motion, and increased net torques and work in all lower limb joints compared to the slower speed. The lack of significant interaction effect on running biomechanics suggested that adding a stiff plate into the shoe did not require specific location among speeds performed in the present study, which mainly corresponded to speeds performed by recreational runners (Gordon et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…It is surprising that most reports investigating exhausting running have focused on CoM kinetics, although it is known that CoM work is the result of a complex interaction of the joint work done by individual muscles, especially at the lower extremity (20,21). A joint-specific view allows to describe the individual contributions of different muscle groups to the total work of the lower extremity (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…To test the performance of this method, I added drift to a 30-second vertical GRF signal collected by an instrumented treadmill during running (Fukuchi, Fukuchi, & Duarte, 2017). Using dryft to reduce this vertical GRF signal's drift produced favorable results, as the average (± SD) force measured across the extracted aerial phases values was -0.01 N (± 0.09 N) for the corrected signal ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%